Fingerprint ridge orientation estimation using a modified Canny Edge Detection Mask - Phillips, Laurice; Bernard, Margaret (My University, 2012)
Fingerprint recognition is arguably the most popular biometric used in authentication of individuals today. One critical step in the process of automatic fingerprint recognition is the segmentation of a digital fingerprint image into smaller regions where local image features can be more easily enhanced, analyzed or extracted. In this process it is essential to accurately estimate the fingerprint ridge orientation within the local region so that the fingerprint’s core singular points can be identified. This research paper proposes a novel approach to estimating the local ridge orientation by using an image convolution operation based on a Canny Edge detection mask. Experimental results illustrate the effectiveness of the algorithm in establishing the dominant edge direction of the ridge.
Keywords: Segmentation; Canny Edge Detection Mask; Edge direction; Segment orientation